Shared-optical-path VLBI frequency phase transfer from 86 to 258 GHz on an 8600km baseline: Demonstrated with the APEX and IRAM 30m telescopes - Zhao, G. -Y; Roy, A. L.; Wagner, J. F.; Donoso, E.; Torne, P.; Ros, E.; Lindqvist, M.; Lobanov, A. P.; Ramakrishnan, V.; Krichbaum, T. P.; Rottmann, H.; Zensus, J. A.; et al. (EDP Sciences, 2026)
Context
The receiver N3AR operating at a frequency range between 67 and 116 GHz was commissioned at the APEX telescope in October 2024. It adds a new low-frequency band for APEX, with the capability of simultaneous dual-frequency observations using a dichroic beamsplitter. The 3 mm receiver also allows APEX to join the existing 3 mm global very long baseline interferometry (VLBI) network.
Aims
One of our commissioning goals was to perform simultaneous dual-band VLBI observations at 86 and 258 GHz using receivers with shared optical paths (SOPs) to correct the atmospheric phase fluctuations using the frequency phase transfer (FPT) technique. This was possible together with the IRAM 30 m telescope, which has already developed such a capability. We aimed to verify the expected phase coherence and sensitivity improvement at the higher frequency achievable by applying FPT.
Methods
With the dual-band, single baseline data, we applied the FPT method, which uses the lower-frequency data to correct the simultaneously observed higher-frequency data. We evaluated the improvement compared to the conventional single-band observing mode by analyzing the coherence factor in the higher-frequency data.
Results
Our results show that the phase fluctuations at the two bands correlate well. After applying FPT, the interferometric phases at the higher frequency vary much less, and the coherence factor is significantly improved.
Conclusions
Our analysis confirms the feasibility of applying FPT to frequencies above 250 GHz with SOP receivers. Future observations in this mode could dramatically improve the sensitivity and imaging fidelity of high-frequency VLBI.